Relationship between quality of work life and career advancement among Iranian academics - Parsa, Bita; Idris, Khairudin; Abu Samah, Bahaman; Abdul Wahat, Nor Wahiza; Parisa, Parsa (Elsevier, 2014)
Background and aims: Career advancement can lead to productivity and success of educational canters and universities. Academic employees have a significant role in the community education and social development. Success in universities depends on academic employee's career advancement and quality of workplace. Quality of work life (QWL) views the organizational environment in accordance with employees’ needs (health and safety, economic and family, social, esteem, actualization, knowledge and aesthetic). This study investigated the relationship between QWL and career advancement among academic employees in Hamadan, Iran. Methods: The structured questionnaires were based on information of 307 randomly selected academics in two Hamadan public universities in year 2013. The data collection was based on a self-administered questionnaire including background characteristics, seven dimensions of quality of work life and four dimensions of career advancement. Data was analyzed with structural equation modelling (AMOS) method. Results: The mean age of respondents was 39.67 (7.4) years. Most of them had Ph.D (70%) and 30% had M.Sc. educational level. Majority of respondents perceived moderate level of QWL (73%) and perceived high level of career advancement (62.2%). The results of the patch analysis showed that quality of work life and career advancement was significantly and positively related (ß=.28, P=.039). Conclusions: It can be concluded that there was a positive and significant relationship between quality of work life and career advancement. The results of the study supported this idea that higher quality of work life lead to higher career advancement. Therefore, improving quality of work life of academics in universities might have high impact on educational and community development in country.